Amplify-and-forward cooperative diversity with space-time coded UWB systems - Abou-Rjeily, Chadi (2017)
In this paper, we examine the impact of spatial diversity on ultra-wideband (UWB) systems. This diversity is exploited by deploying two antennas at the UWB terminals. For single-antenna systems, spatial diversity is exploited in a distributed manner where a neighboring node can help the source in delivering its message to a destination. In particular, two space-time (ST) coding schemes are proposed. The first one is optimal among all totally-real codes having a constant transmitted energy per antenna. Unlike the classical approach of constructing ST codes over infinite fields, the second construction takes the structure of 2-dimensional constellations into consideration in order to propose an appropriate modulation-specific code. These schemes are associated with multi-antenna arrays and with virtual arrays based on the amplify-and-forward (AF) strategy